The Flash animator - Corsaro, Sandro (New Riders Pub., 2002)
Intrigued by digital animation? Know a little bit about Macromedia Flash but are ready to take it to the next level? The Flash Animator will teach you how to create traditional-looking animations faster, cheaper, and with more delivery options. Sandro Corsaro helps you to develop a solid understanding of the principles of traditional animation, and then guides you step by step through bringing those principles to life with Flash. Topics range from creating basic ball bounces to managing complex character design, sound, and optimization issues. Interviews with numerous experts in the animation industry--complete with beautiful artwork and insights from feature-film animators and Web pioneers--are included to inspire you along your Flash animation path. Interviewees include: Iwao Takamoto, creator of Scooby Doo; Brad Abelson, Storyboard Artist, The Simpsons; Joe Shields, Joe Cartoon; Tom Winkler, Doodie.com; And many other influential animators. The CD contains all source files for the book's examples, exclusive animation files, and bonus Macromedia Flash cartoons. There is also an in-depth audio interview with Iwao Takamoto.